Philadelphia chromosome positive AML arising from JAK2-positive myelofibrosis - Marte Karen Brattås; Kyrre Lilleeng; Randi Hovland; Ingvild Jenssen Lægreid; Marta Vorland; Friedemann Leh; Øystein Bruserud; Bjørn Tore Gjertsen; Håkon Reikvam (BMC, 2018)
Abstract Background A feature of myeloproliferative neoplasia is transforming to more aggressive and malignant myeloid neoplasia, including acute myeloid leukemia. Different pathogenesis mechanisms participate in transformation, including transformation of existing potential preleukemic clones, since JAK2-mutant myeloproliferative neoplasms often transform to JAK2 wild-type acute myeloid leukemia. Case presentation Here, we present an 80 year old man with a JAK2-V617F mutant primary myelofibrosis. After 10 months the disease transform into a Philadelphia chromosome positive acute myeloid leukemia, detecting the cytogenetic aberration; t(9;22)(q34;q22) encoding the rare BCR-ABL1 fusion gene; e6a2. The patient had treatment response to tyrosine kinases, illustrating the potential benefits of such approach in treating these patients subset. Conclusion The case illustrates the potential of leukemic transformation to Philadelphia chromosome positive myeloid malignancies from potential existing preleukemic clones, and the awareness of such an evolution among patients with myeloproliferative neoplasms. Tyrosine kinases have potential effect also in patients presenting without chronic myeloid leukemia and with rare BCR-ABL1 fusion transcripts, and should probably be a part of the treatment approach.